Technical Factors Influencing to Instant Powder from Strawberry (Fragaria) Juice - N. P. Minh (Journal of Global Pharma Technology, 2016)
Strawberry (Fragaria), a rich source of phytochemicals (ellagic acid, anthocyanins, quercetin, and catechin) and vitamins (ascorbic acid and folic acid), has been highly ranked among dietary sources of polyphenols and antioxidant capacity. Bioactive compounds in strawberry revealed high abundance of anthocyanins, flavonols, flavanols, and cinnamic acid.  To increase strawberrys popularity and expand their use in the food industry, it’s neccesary to explore the appropriate postharvest handling and storage.The aim of this work was to study the feasibility of spray drying of strawberry juice juice. Various characteristics of spray-dried fruit juice powders are well affected by spray-drying conditions including inlet air temperature, out let air temperature, feed flow rate, drying carrier agent. Results revealed that inlet/ outlet spray drying temperature (155oC: 85oC), speed flow rate (12 ml/ min), γ‐cyclodextrin: maltodextrin (4: 6 % w/v) were appropriated for spray drying of dried strawberry powder from its juice. The spray-dried product of γ‐cyclodextrin-maltoxetrin-strawberry juice was considered to be the good technique to dry strawberry juice on the result of phytochemical determination, physical and chemical properties and antioxidant activity. Value addition of strawberry juice has been created by changing in the physical form of the agricultural produce which leads to its greater acceptability, extended availability, enhanced market viability and increased cost to benefit ratio for the grower of the strawberry produce.Keywords: Strawberry juice, Spray drying, Dried powder, Inlet air, Out let air, Speed flow rate, γ‐cyclodextrin, maltodextrin.